Polish Interwar [Non]Democracy from the View-Point of Julije Benešić - Pieniążek-Marković, Krystyna (Poznańskie Studia Slawistyczne, 2019)
In the article, the image of Polish democracy/autocracy during the Second Republic has been reconstructed. The subject of the analysis were the autobiographical notes entitled Osam godina u Varšavi written by Julije Benešić who stayed in Warsaw in the years 1930–1938 as a delegate of the Yugoslavian Department of Eductaion and Science. From his currently updated notes, a picture of Poland emerged as a state in which the basic civil rights were regularly broken including those guaranteed by the Constitution. The most glaring examples of the non-democratic actions regarded the problems of the national minorities (specifically the Polish-Ukrainian and Polish-Jewish relationships) as well as the prisons for the political opponents (Bereza Kartuska and Brześć). What is more, the observations made by the Croatian translator, writer and linguist illuminate in the form of interesting conotations the Polish mentality.